Failure Analysis of Bonded Composite Pipe Joints Subjected to Internal Pressure and Axial Loading. (2016) - Das, R.R.; Baishya, N.
Abstract: Three dimensional stress analysis of bonded socket joints with laminated FRP composite pipes as adherends has been carried out in the present research. Influence of internal pressure conditions which are most commonly experienced during flow of various fluids, has been taken into account in the present investigation. Finite Element Method (FEM) based modelling and simulation techniques developed in the present study is capable of carrying out a detailed study of three-dimensional stresses along with fracture analysis of the bonded joint. Tsai-Wu coupled stress criteria have revealed that, free edges of adhrend-adhesive interfaces are vulnerable to adhesion failure under the influence of pressure. Finally, a suitable stacking sequence has been suggested leading to improved fracture resistance at the bonded joint.